2006
DOI: 10.1111/j.1083-6101.1998.tb00093.x
|View full text |Cite
|
Sign up to set email alerts
|

Audiographic Telecourses for the Web: An Experiment

Abstract: Prior research on instructional media effects suggested that an audiographic approach to World Wide Web based courses would optimize educational effectiveness along with cost effectiveness, although with a possible loss of teacher immediacy that could adversely affect student attitudes. An introductory telecommunication course was converted to an audiographic Web telecourse in which students listened to pre‐recorded audio classroom interactions while viewing a detailed course outline and illustrative sites ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 28 publications
0
38
0
1
Order By: Relevance
“…Instruction over the Internet is perceived by many to be a significant breakthrough in teaching and learning [18,34,[36][37][38]. Internet technology facilitates the exchange of information and expertise and provides opportunities for learners in remote and disadvantaged locations [29,58].…”
Section: The Internet Learning and Tammentioning
confidence: 99%
“…Instruction over the Internet is perceived by many to be a significant breakthrough in teaching and learning [18,34,[36][37][38]. Internet technology facilitates the exchange of information and expertise and provides opportunities for learners in remote and disadvantaged locations [29,58].…”
Section: The Internet Learning and Tammentioning
confidence: 99%
“…At least as it relates to personality types represented in this study, online programs may have a much wider array of personality types than those found in traditional programs. Across all programs, research has been unable to demonstrate any significant differences in learning when comparing students in online and traditional programs [70][71][72][73]. The greater number of information technology programs, and degree programs as well, being taught through distance education, usually over the Internet, to nontraditional students is a growing challenge for teachings [62].…”
Section: Improve Teaching Methodsmentioning
confidence: 99%
“…While the majority of CMC is text-based, there is a small but growing body of research comparing traditional face-to-face lecture courses to audiographic and desktop videoconferencing (Chidambaram & Jones, 1993;Alavi et al, 1995;Larose et al, 1998). Chidambaram & Jones (1993) compared the effects of CMC, face-to-face, and audio conferences on student decision making.…”
Section: Media Comparison Researchmentioning
confidence: 99%
“…Participants in the audio conferencing condition performed slightly better than participants in the other two conditions. Larose et al (1998) compared different sections of a telecommunication course employing lecture discussions or audio discussions recorded for a web course section. No differences in student attitude or performance were found.…”
Section: Media Comparison Researchmentioning
confidence: 99%